Hydrolytic mechanism of OXA-58 enzyme, a carbapenem-hydrolyzing class D β-lactamase from Acinetobacter baumannii - Verma, Vidhu (2011)
Carbapenem-hydrolyzing class D β-lactamases (CHDLs) represent an emerging antibiotic resistance mechanism encountered among the most opportunistic Gram-negative bacterial pathogens. We report here the substrate kinetics and mechanistic characterization of a prominent CHDL, the OXA-58 enzyme, from Acinetobacter baumannii. OXA-58 uses a carbamylated lysine to activate the nucleophilic serine used for β-lactam hydrolysis. The deacylating water molecule approaches the acyl-enzyme species, anchored at this serine (Ser-83), from the α-face. Our data show that OXA-58 retains the catalytic machinery found in class D β-lactamases, of which OXA-10 is representative. Comparison of the homology model of OXA-58 and the recently solved crystal structures of OXA-24 and OXA-48 with the OXA-10 crystal structure suggests that these CHDLs have evolved the ability to hydrolyze imipenem, an important carbapenem in clinical use, by subtle structural changes in the active site. These changes may contribute to tighter binding of imipenem to the active site and removal of steric hindrances from the path of the deacylating water molecule.